Profil kondisi fisik ekstrakulikuler dayung SMA KORPRI Kota Bekasi - Wicaksono, Faris; Abidin, Dindin (Motion: Journal Research of Physical Education, 2022)
The purpose of this study was to determine how the physical condition of the Bekasi City Korpri High School Rowing Extracurricular. The method in this study the author used a descriptive method. In this study, researchers used a survey method using physical condition test data collection techniques (ANTHOPOMETRY) which contained 7 test items, namely: (1) 30 meter running test. (2) Vertical Jump Test (3) 12-minute running test (4) Sit Up Test (5) Pull Up Test (6) Sitting on the wall test (7) Sit and Reach Test. By using the total sampling technique. The number of sempel used is all 14 students of the Bekasi City Korpri High School Rowing Extracurricular. The results of this study indicate that the level of physical condition of the Bekasi City Korpri High School Rowing Extracurricular is in the Fair category, namely 100%. From the results of this study, suggestions can be given, namely the need for more training. More training means an increase in physical condition training developed by the Bekasi City Korpri High School Rowing Extracurricular coach, in order to improve the physical condition specifically for students because to get achievements clearly requires better physical quality. For this reason, it is necessary for the Bekasi City Korpri High School Rowing Extracurricular coach to provide regular training for Bekasi city referees.